Zona incerta projection neurons and GABAergic and GLP-1 mechanisms in the nucleus accumbens are involved in the control of gastric function and food intake. (April 2020) - Wang, Qian; Zhang, Xiaoqian; Leng, Hui; Luan, Xiao; Guo, Feifei; Sun, Xiangrong; Gao, Shengli; Liu, Xuehuan; Qin, Hao; Xu, Luo
Abstract: Objective: Our aim was to explore the effect of γ-aminobutyric acid (GABA) signaling in the nucleus accumbens (NAc) on promoting gastric function and food intake through glucagon-like peptide 1 (GLP-1)-sensitive gastric distension (GD) neurons under the regulatory control of the zona incerta (ZI). Methods: GABA neuronal projections were traced using retrograde tracing following fluorescence immunohistochemistry. An extracellular electrophysiological recording method was used to observe the firing of neurons in the NAc. HPLC was used to quantify the GABA and glutamate levels in the NAc after electrical stimulation of the ZI. Gastric functions including gastric motility and secretion, as well as food intake, were measured after the administration of different concentrations of GABA in the NAc or electrical stimulation of the ZI. Results: Some of the GABA-positive neurons arising from the ZI projected to the NAc. Some GABA-A receptor (GABA-AR)-immunoreactive neurons in the NAc were also positive for GLP-1 receptor (GLP-1R) immunoreactivity. The firing of most GLP-1-sensitive GD neurons was decreased by GABA infusion in the NAc. Intra-NAc GABA administration also promoted gastric function and food intake. The responses induced by GABA were partially blocked by the GABA-AR antagonist bicuculline (BIC) and weakened by the GLP-1R antagonist exendin 9–39 (Ex9). Electrical stimulation of the ZI changed the firing patterns of most GLP-1-sensitive GD neurons in the NAc and promoted gastric function and food intake. Furthermore, these excitatory effects induced by electrical stimulation of the ZI were weakened by preadministration of BIC in the NAc. Conclusion: Retrograde tracing and immunohistochemical staining showed a GABAergic pathway from the ZI to the NAc. GABAergic and GLP-1 mechanisms in the NAc are involved in the control of gastric function and food intake. In addition, the interaction (direct or indirect) between the ZI and these NAc mechanisms is involved in the control of gastric function and food intake. Highlights: GABAergic neurons in the NAc received afferent information from the stomach regarding gastric distension. GABAergic and GLP-1 mechanisms in the NAc are involved in the control of gastric function and feeding, regulated by the ZI. Retrograde tracing and immunohistochemistry staining showed a GABAergic pathway from the ZI to the NAc. Some GABAergic neurons from the ZI enhanced gastric function and food intake by releasing GABA into the NAc, and GLP-1 receptor signaling played an important role in the regulatory process.